Mobile journalism: Systematic literature review - López-García, Xosé (2019)
Submitted by Canavilhas (jc@ubi.pt) on 2019-02-26T19:45:55Z No. of bitstreams: 1 2019_ARTIGO_Mobile journalism_Systematic literature review.pdf: 213852 bytes, checksum: a36644c86f12fe8bf69eb915410ca152 (MD5)